(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Agricultural productivity is winding up progressively imperative issue as the total populace keeps on developing. India, one of the world’s most crowded countries, has made strides in the previous decades to build its land productivity. Agriculture still structures the foundation of Indian economy, in hate concerned endeavors towards industrialization in most recent three decades. Agriculture contributes a high offer of net domestic product by sectors in India. Access to water is a critical factor for the survival of Indian farmers in villages. Irrigation is one of the major arranged endeavors of any nation’s expanded agricultural production. It around pairs the yield of the land contrasted with those depending just upon the downpours. Canal irrigation is increasingly broad and proficient when contrasted with well or tank irrigation systems. In this article, we considered the degree of advantages got from drip irrigation in horticultural crops and distinguish the requirements experienced by farmers in receiving the drip irrigation for horticultural crops. In this article we gave an overview of benefits of Drip Irrigation in Horticultural Crops.